2009
DOI: 10.1021/nl9004805
|View full text |Cite
|
Sign up to set email alerts
|

Superplastic Nanowires Pulled from the Surface of Common Salt

Abstract: Superplastic nanowires were formed by touching the NaCl(100) surface with a Au tip in a transmission electron microscope. The nanowires were stretched < or =2.2 microm, or 280%, and bent >90 degrees upon compression, when showered with the electron beam. More surprisingly, no dislocations were observable during the elongation due to fast diffusion. Mechanical measurements in humid atmospheres suggest that salt nanowires also form in ambient environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 35 publications
(75 reference statements)
1
42
0
Order By: Relevance
“…The forces on approach at the lowest biases (<3 V, Figure 2) are characteristically similar to those observed earlier with IFM involving capillary condensation between other insulating surfaces, including NaCl, diamond, poly(vinyl acetate) and carboxylated self-assembled monolayers (SAMs), 10,11,41,42 supporting that the transition at D* stemmed from capillary condensation and not from electrical discharge. Both the discontinuity in the force at D* and the linear scaling of the force with separation for D < D* are established features of capillary nanobridges at constant vapor pressure (for reviews of surface forces, see refs 3, 8, 22, and 43).…”
Section: ' Methods and Materialssupporting
confidence: 83%
See 1 more Smart Citation
“…The forces on approach at the lowest biases (<3 V, Figure 2) are characteristically similar to those observed earlier with IFM involving capillary condensation between other insulating surfaces, including NaCl, diamond, poly(vinyl acetate) and carboxylated self-assembled monolayers (SAMs), 10,11,41,42 supporting that the transition at D* stemmed from capillary condensation and not from electrical discharge. Both the discontinuity in the force at D* and the linear scaling of the force with separation for D < D* are established features of capillary nanobridges at constant vapor pressure (for reviews of surface forces, see refs 3, 8, 22, and 43).…”
Section: ' Methods and Materialssupporting
confidence: 83%
“…While others have shown that the rupture of a nanoscale capillary between separating surfaces is accompanied by an abrupt decrease in the attractive force, no such discontinuities in the forceÀdistance curves were observed here. 9,11,12 Thus, the applied field leads to an electrostatic force that appears to dominate over the capillary interaction during at least the majority of the approach and separation. Importantly, the attractive force measured during separation appears to have the same functional form at both bias levels ( Figure 4).…”
Section: ' Methods and Materialsmentioning
confidence: 99%
“…33 A recent in situ TEM study on NaCl NWs also observed superplastic deformation, and the authors confirmed that electron beam irradiation enhanced ductility. 47 Another example on the superplasticity comes from carbon nanotubes (CNTs). In situ TEM tension experiments showed that, at high temperatures, individual single-walled CNTs can undergo superplastic deformation (becoming nearly 280% longer than its original length, much larger than the theoretical strain of CNTs at room temperature).…”
mentioning
confidence: 99%
“…In situ transmission electron microscopy (TEM) [5][6][7][8] and molecular dynamics (MD) studies [9][10][11][12][13] showed that the plasticity of metallic NWs deformed under vacuum is controlled by the nucleation and escape of dislocations from the free surfaces, and required application of stresses a few orders of magnitude higher than necessary for the dislocation glide mechanisms of bulk crystalline materials. Alternatively, amorphous NWs may become superplastic at room temperature and can form long atomic chains at the fracture surfaces 14,15 . Consequently, statements such as 'smaller is stronger' 4,[16][17][18][19][20] , 'smaller is superplastic' 14,15,21 or 'smaller is softer' 22 , have been used to describe mechanical properties of nanomaterials.…”
mentioning
confidence: 99%
“…Alternatively, amorphous NWs may become superplastic at room temperature and can form long atomic chains at the fracture surfaces 14,15 . Consequently, statements such as 'smaller is stronger' 4,[16][17][18][19][20] , 'smaller is superplastic' 14,15,21 or 'smaller is softer' 22 , have been used to describe mechanical properties of nanomaterials. In general, sophisticated tensile and compression tests of NWs were carried out in vacuum chambers, and thus, the effects of environment on their mechanical properties were not considered.…”
mentioning
confidence: 99%